TRANSACTIONAL COSTS OF INTELLECTUAL CAPITAL OF NON-STATE UNIVERSITIES - N. V. Kochetkova (Russian Journal of Economics and Law)
The article views the hierarchical structure of intellectual capital, defines the main types of transactional costs referring to the intellectual capital of non-state universities.